2007
DOI: 10.1177/154405910708600409
|View full text |Cite
|
Sign up to set email alerts
|

MMPs, IL-1, and TNF are Regulated by IL-17 in Periodontitis

Abstract: Periodontitis is characterized by periodontal tissue destruction. Since interleukin-17 (IL-17) has been reported to up-regulate IL-1beta and tumor necrosis factor-alpha (TNF-alpha), it was hypothesized that it is increased in periodontitis and up-regulates these cytokines and tissue-destructive matrix metalloproteinases (MMP) in local migrant and resident cells. Immunocytochemistry disclosed elevated IL-1beta, TNF-alpha, and IL-17 levels in periodontitis. These cytokines induced proMMP-1 and especially MMP-3 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
192
1
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(222 citation statements)
references
References 35 publications
16
192
1
13
Order By: Relevance
“…A direct interaction between MMP9 and IL-8 has been reported in hematopoietic stem cell trafficking in liver injury (17,20), in retinoic acid syndrome (45), and in leucocytes (51). Beklen et al (7) showed that there was an upregulation of both MMP9 and IL-8 in periodontitis. Many studies related with airway epithelium have shown a direct link between the IL-8 secretion and MMP9 expression (15,31,55).…”
Section: Discussionmentioning
confidence: 99%
“…A direct interaction between MMP9 and IL-8 has been reported in hematopoietic stem cell trafficking in liver injury (17,20), in retinoic acid syndrome (45), and in leucocytes (51). Beklen et al (7) showed that there was an upregulation of both MMP9 and IL-8 in periodontitis. Many studies related with airway epithelium have shown a direct link between the IL-8 secretion and MMP9 expression (15,31,55).…”
Section: Discussionmentioning
confidence: 99%
“…Novel proinflammatory cytokine IL-17 has recently become implicated in CHF 10 . Animal models demonstrated that IL-17 is essential for the development of dilated cardiomyopathy, probably by stimulating fibrosis through direct and/or indirect induction of MMP1/2/3/9 10,11 . IL-17 is also required for the sustained expression of IL-6 during myocarditis 27 .…”
Section: Chf Patientsmentioning
confidence: 99%
“…The neutralization of IL-17 reduces myocarditis severity 9 and has an essential role in the development of dilated cardiomyopathy 10 . Th17 cells infiltrate the inflamed heart and are responsible for heart-specific up-regulation of IL-6, TNFα, IL-1β, which can promote fibrosis, either directly or indirectly, by inducting matrix metal proteases 1, 2, 3 and 9 10,11 . Moreover, TNFα and IL-17 act synergistically to create a proinflammatory environment 12 .…”
mentioning
confidence: 99%
“…Inflammatory cytokines inhibit BMP-induced osteogenesis and bone formation (17,18); in fact, TNF␣ is a major inflammatory mediator responsible for bone loss in a number of bonerelated inflammatory diseases (19,20). TNF␣ inhibits BMP signaling by interfering with the DNA-binding ability of Smads via activation of the nuclear factor-B (NF-B) pathway, regulating Runx2 expression, and inhibiting BMP-induced osteoblast differentiation (18,21,22).…”
Section: Bmp2mentioning
confidence: 99%